Sustained Fibrinolysis After Administration of t-PA Despite Its Short Half-Life in the Circulation - Eisenberg, Paul R; Sherman, Laurence A; Tiefenbrunn, Alan J; Ludbrook, Philip A; Sobel, Burton E; Jaffe, Allan S (Thrombosis and Haemostasis, 1987)
To characterize the duration of the fibrinolytic response to tissue-type plasminogen activator (t-PA) and streptokinase (SK) in patients with acute myocardial infarction we serially assayed crosslinked fibrin degradation products (XL-FDP) and Bβ15-42 fibrinopeptide. Use of specific monoclonal antibodies permitted quantification and differentiation of fibrin from fibrinogen degradation products. Marked elevations of XL-FDP occurred within 1 hour after administration of t-PA (n = 13) or SK (n = 35) to >1000 ng/ml in 79% of the patients. All patients given t-PA exhibited elevations of XL-FDP >1000 ng/ml, most exhibited values >5000 ng/ml (79% of patients). In contrast 6 of the patients given SK failed to exhibit XL-FDP >1000 ng/ml. XL-FDP >5000 ng/ml occurred in only 14%. The difference in the response to t-PA compared to SK was particularly striking 7 hours or more after administration of activator at which time XL-FDP were markedly elevated in patients given t-PA (5821 ± 1683 ng/ ml) compared with decreasing values in patients given SK (2924 ± 1186 ng/ml) (p <0.01). Levels of Bβ315-42 were significantly higher after t-PA compared with SK beginning 3 hours after treatment, consistent with a greater intensity of fibrinolytic response to t-PA. Marked elevations of this short lived degradation product of fibrin (t1/2 = 10-20 minutes) in the samples drawn late after administration of t-PA (44.3 ±12.8 nM) but not after SK (11.7 ± 4.5 nM) confirmed prolonged fibrinolytic activity of plasmin after t-PA. There was no discernible relationship between the extent of fibrinolysis as assessed by XL-FDP and Bβ 15-42 and the total dose of t-PA administered or the duration of the infusion. Elevations of XL-FDP invariably occurred after SK, and were not significantly different in patients with or without recanalization. Thus “clinical success” of coronary thrombolysis appears to depend on a favorable balance between thrombosis and fibrinolysis rather than the intensity of fibrinolysis alone. The prolonged fibrinolytic activity after t-PA appears to reflect the enhanced binding of this activator to fibrin and is likely to result in more sustained and hence more effective fibrinolysis with t-PA compared to SK despite the short half-life of t-PA (t1/2 = 6 minutes) in the circulation.
Keywords: Thrombolysis; Fibrin degradation products; Fibrinopep-tides; Myocardial infarction